Incorporating Higher-Order Thinking Skills In The Indonesian Language Curriculum At Islamic Religious Universities - Mirnawati, Mirnawati; Yaumi, Muhammad; Halimah, Andi; Mardiana, Mardiana; Ahmad, Djuwairiah; K, Munawir; Rosdiana, Rosdiana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Learning Indonesian in higher education, especially at IAIN Palopo, faces significant challenges due to the lack of appropriate and effective teaching materials, so it is necessary to develop teaching materials based on higher-order thinking Skills (HOTS) to improve the quality of learning and students' language skills. This study aims to develop and evaluate Indonesian language teaching materials based on higher-order thinking Skills (HOTS) to improve the quality of learning and language skills of students at the Faculty of Tarbiyah and Teacher Training, IAIN Palopo. This study uses the Research and Development (R&D) method with the Borg and Gall design to develop Indonesian language teaching materials based on higher-order thinking Skills (HOTS) at the Faculty of Tarbiyah and Teacher Training, IAIN Palopo. The research process involves the development, validation by experts, and revision of teaching materials, with data collected through validation sheets and analyzed using the Aiken index to measure validity. This research has successfully developed Indonesian language teaching materials entitled